#MATERNIDADESEMJULGAMENTOS: negociações de sentidos sobre culpa e amor materno entre consumidoras de O Boticário (Intercom - Brazilian Journal of Communication Sciences, 2024)
This article explores interpretations of the meanings related to the Motherhood Without Judgments campaign, launched in 2022 by the brand O Boticário. The proposal is to discuss how advertising enables the study of the circulation of meanings about motherhood, mothering, and its consequences in women's lives, considering the context and sociocultural values. The social representations and the encoding/decoding model of Stuart Hall (2009) bases the theoretical and methodological framework, which we applied in the interpretative analysis. The empirical material consists of 92 posts. Results indicate that the advertising discourse interacts with consumers in a discursive space, where the hegemonic sense of patriarchal motherhood prevails. We also observed contestation practices and the production of a political vision on motherhood and mothering, which questions the social structure and gender, race, and class inequalities.